Предмет: Алгебра,
автор: Kulkiovdanila
Упростите выражение
(а-2)(а-1)-а(а+1)=
(б-5)(б+10)+(б+6)(б-8)=
(2с+3)(3с+2)-(2с+7)(2с-7)=
(3д+5)(5д-1)-(6д-3)(2-8д)=
Ответы
Автор ответа:
0
(а-2)(а-1)-а(а+1)= а^ 2 - 3 a + 2 - a ^ 2 - a = - 4 a + 2
(б-5)(б+10)+(б+6)(б-8)= b ^2+5b-50 +b^2 -2b -48= 2b^2 +3b - 98
(2с+3)(3с+2)-(2с+7)(2с-7)= 6 c^2 + 4 c + 9 c + 6 - 4 c ^2 + 49 = 2 c^2 + 13 c + 55
(3д+5)(5д-1)-(6д-3)(2-8д)=
15d^2 -3d + 25 d - 5 - ( 6 d - 48d - 6 + 24 d) = 15d^2 -3d + 25 d - 5 -
- 6 d + 48d + 6 - 24d = 15d^2+ 40 d + 1
(б-5)(б+10)+(б+6)(б-8)= b ^2+5b-50 +b^2 -2b -48= 2b^2 +3b - 98
(2с+3)(3с+2)-(2с+7)(2с-7)= 6 c^2 + 4 c + 9 c + 6 - 4 c ^2 + 49 = 2 c^2 + 13 c + 55
(3д+5)(5д-1)-(6д-3)(2-8д)=
15d^2 -3d + 25 d - 5 - ( 6 d - 48d - 6 + 24 d) = 15d^2 -3d + 25 d - 5 -
- 6 d + 48d + 6 - 24d = 15d^2+ 40 d + 1
Похожие вопросы
Предмет: Математика,
автор: elubizbajka
Предмет: Английский язык,
автор: nurdauletas01
Предмет: Математика,
автор: patriot2018ua
Предмет: Биология,
автор: MixailTolmachev
Предмет: Алгебра,
автор: Akiro303